The Correlation Between Students’ Speaking Anxiety and Their Speaking Ability: A Quantitative Study at Islamic Junior High School Sunan Giri - Siti Sintiawati Sholikhah; Shierly Novalita Yappy; M. Khusni Mubarok (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the correlation between students’ speaking anxiety and their speaking ability in an English as a foreign language (EFL) context, focusing on seventh grade learners at MTs Sunan Giri, Kediri. The problem addressed in this research is the persisting assumption that higher levels of anxiety negatively affect learners’ oral performance, while limited empirical evidence exists in Indonesian lower secondary school settings. The objective of the study is to measure students’ anxiety levels using a speaking anxiety questionnaire and to assess their speaking ability through a rubric based speaking test in which students presented either a poster or the topic “part of the house.” Using a quantitative correlational design, data from fourteen students were analyzed using descriptive statistics and Pearson’s product–moment correlation. The results show that the students had moderate levels of speaking anxiety (M = 62.14; SD = 4.61) and moderate speaking ability scores (M = 45.36; SD = 9.30). Pearson’s analysis revealed a moderate positive correlation between speaking anxiety and speaking ability, r = 0.502, p = 0.067, while Spearman’s rho yielded a similar result (ρ = 0.522, p = 0.055). Although the correlation did not reach statistical significance at the 0.05 level, the positive direction of the relationship suggests that in this small sample, higher anxiety scores were associated with higher speaking performance, a pattern that differs from most theoretical predictions. These findings highlight the importance of reexamining the complexity of classroom anxiety, task type, and learner characteristics, particularly in small group settings. The study contributes to the growing literature on affective factors in EFL speaking and suggests the need for larger scale research to confirm the trend observed in this study.